Upconversion and cooperative luminescence in YBO3:Yb3+- Er3+. (June 2021) - Rivera-López, F.; Torres, M.E.; Gil de Cos, G.
Highlights: Upconversion and cooperative luminescence is reported in YBO3 :Yb 3+ - Er 3+ . The observed red and green upconverted bands are emissions from Er 3+ ions. The obtained blue cooperative luminescence is associated to Yb 3+ -pairs. Impurities of Tm 3+ ions can be discarded. The color diagram is presented, obtaining a dominant green emission color purity. Abstract: This paper reports the frequency upconversion and cooperative luminescence in YBO3 :Yb 3+ -Er 3+ sample. After cw diode laser excitation, at 980 nm, three clear bands were observed at around 650, 545 and 484 nm, corresponding to red, green and blue emissions, respectively. The bands centred at 650 and 545 nm can be attributed to upconversion emissions from Er 3+ ions. Mechanisms of energy transfer upconversion and excited-state absorption of pump radiation are proposed in order to explain these radiative transitions. The blue emission at 484 nm is analysed with the aim to elucidate if it can be attributed to cooperative luminescence from Yb 3+ -pairs. Finally, the color diagram is presented so as to study the color purity of the sample.